Microplastic exposure and allergic rhinitis: Network toxicology, and molecular docking insights - Yaojun Wang; Dandan Xu (PLoS ONE, 2025)
Background Microplastics (MPs), ubiquitous environmental pollutants, are increasingly associated with global health risks, yet their role in allergic rhinitis (AR) pathogenesis remains poorly understood. Methods Toxicity profiles of four typical MPs (polyethylene [PE], polypropylene [PP], polyvinyl chloride [PVC], polystyrene [PS]) were evaluated using ADMETlab 3.0. MP-related targets and AR-associated genes were integrated from the CTD database and GSE43523 dataset. Functional enrichment (GO/KEGG) and PPI network analysis (STRING/GeneMANIA) were performed on overlapping genes. LASSO regression and expression validation identified key targets, and molecular docking (Autodock Vina) assessed interactions with potential therapeutics predicted by CTD. Results ADMET analysis revealed MPs exhibit significant respiratory toxicity and ocular toxicity. We identified 301 MP toxicity targets, 1,026 AR differentially expressed genes (DEGs), and 15 overlapping pathogenic targets. Functional enrichment (GO/KEGG) demonstrated MPs disrupt respiratory mucosal homeostasis via apoptosis, mitochondrial autophagy, and inflammatory pathways. PPI network analysis and LASSO regression pinpointed DNAJB9, SQSTM1, and MAPK9 as core mediators: these genes were significantly downregulated in AR patients (P < 0.05) and displayed robust diagnostic performance (AUC = 0.82–0.93). Molecular docking revealed resveratrol binds these targets with high affinity, surpassing SQSTM1 (−5.8 kcal/mol) and MAPK9 (−6.8 kcal/mol), suggesting its potential to block MP-induced dysregulation. Conclusions MPs drive AR pathogenesis through respiratory toxicity pathways, with DNAJB9, SQSTM1, and MAPK9 serving as critical molecular mediators. Resveratrol, by modulating target-mediated programmed cell death, emerges as a promising therapeutic candidate for mitigating MP-induced AR.